Protocol for seizure prophylaxis following intracerebral hemorrhage study (SPICH): a randomized, double‐blind, placebo‐controlled trial of short‐term sodium valproate prophylaxis in patients with acute spontaneous supratentorial intracerebral hemorrhage. Issue 6 (12th September 2013) - Hu, X.; Fang, Y.; Li, H.; Liu, W.; Lin, S.; Fu, M.; Li, X.; Cao, X.; Zhang, H.; You, C.; Liu, M.
<x xml:space="preserve">Abstract</x> Rationale Seizures after intracerebral hemorrhage are a common complication and may adversely affect neurological outcome. However, studies are inadequate on the utility of prophylactic anticonvulsant therapy in patients with hemorrhagic stroke, and the results remains controversial. Aims This study aims to determine if short‐duration sodium valproate prevents seizure onset or improves the survival and neurological outcome in adults after acute spontaneous supratentorial intracerebral hemorrhage. Design In this randomized, double blinded, placebo‐controlled trial, 258 patients meeting the inclusion criteria will be enrolled in the Department of Neurosurgery, West China Hospital. In addition to standard care, patients will be randomly assigned to receive seven‐day prophylaxis of sodium valproate 500 mg daily (alternatively 400 mg daily by intravenous infusion in 250 ml 0·9% normal saline) or matching placebo. Patients will be followed up at seven‐days, 3, 6, and 12 months. Study outcomes The primary outcomes are early (≤7 days) and late onset seizures (>7 days). Secondary outcomes include midline shift, enlargement of hematoma, death (all cause), adverse effects, and functional outcome assessed by Glasgow Outcome Scale and modified Rankin Scale. Discussion Given the lack of evidence for seizure prophylaxis in patients with acute supratentorial intracerebral hemorrhage, randomized controlled trials are desperately needed. The results from our study are believed to directly influence future prophylactic anticonvulsant therapy of intracerebral hemorrhage.